Characteristics of functional constipation and analysis of intestinal microbiota in children aged 0–4 in Zunyi region - Shungang Gong; Zhengbo Yu; Yuan Ding; Yue Wang; Xi Li; Shengli Gu (BMC Pediatrics)
Abstract Background Functional constipation (FC) significantly impacts children’s health. This study investigates the prevalence and microbiota characteristics of FC in children aged 0–4 years in Zunyi area. Methods From October to December 2023, 2039 children aged 0–4 years in Zunyi were selected using stratified sampling and cross-sectional survey methods. A questionnaire based on Rome IV diagnostic criteria was used. Twenty-nine children with FC were randomly selected as the functional constipation group (FCG), and 26 healthy children, matched for age, sex, and area, were selected as the control group (CG). Results A total of 2051 questionnaires were collected, with 2039 valid responses. Among them, 151 children had FC, resulting in a prevalence rate of 7.4%. The prevalence rates in boys and girls were 6.6% and 8.5%, respectively, with no significant gender difference (P > 0.05). Alpha diversity analysis revealed higher richness and diversity of intestinal flora in the FCG compared to the CG. At the phylum level, Actinobacteria, Firmicutes, Proteobacteria, and Bacteroidetes were dominant in both groups. The FCG showed a higher relative abundance of Firmicutes, Actinobacteria, and Proteobacteria compared to the CG (P < 0.05). Conclusions The prevalence of FC in children aged 0–4 years in Zunyi is 7.4%. Disease characteristics vary with age and living environment but are unrelated to gender. The gut microbiota of children with FC shows significant alterations, with higher diversity and specific phyla abundance.